The Effectiveness Of (Esa) Engage Study Activate Method On Student’s Speaking Ability At The Eight Grade Students Of Islamic Junior High School of Syech Abdul Qadir Al Jailani - Fifin Andika Aprilia; Ainol Ainol; Achmad Kholili (Pascasarjana Universitas Negeri Makassar, 2023)
The study investigates the effectiveness of the Engage-Study-Activate (ESA) method on the speaking ability of eighth-grade students at Islamic Junior High Schools. A quasi-experimental design was employed, involving a pre-test/post-test control group design. The study took place at Mts Sirajut Thalibin Racek Junior High School, which included two classes with a total of 48 students. Class VIII A, the experimental group, consisted of 24 female students, while Class VIII B, the control group, was made up of 24 male students. In this study, data collection was conducted using observation, tests (including pre-tests and post-tests), and documentation. Descriptive statistical analysis was employed to analyze the data. The statistical analysis aimed to determine the mean, frequency, total score, standard deviation, and percentage. The pre-test values for the experimental and control classes were 57.29 and 48.33, respectively, while the post-test values were 83.96 for the experimental class and 60.00 for the control class. The average scores reveal that the experimental group, taught using the ESA method, outperformed the control group, which did not employ the ESA method. Based on data analysis and research findings, it can be concluded that the ESA method significantly improved students' speaking abilities. This is evidenced by the experimental group's average score of 76.36 compared to the control group's average score of 61.82. The mean value of the experimental group is higher than that of the control group, and the t-test value is 3.754, with a 2-tailed significance of 0.001. This suggests that the ESA method can be effectively integrated into speaking instruction in Islamic Junior High Schools to enhance students' speaking proficiency. The study's implications include the importance of adopting learner-centered approaches in language instruction to foster better communication skills in students.Â